Knowledge and stigma towards people living with HIV/AIDS: A study among dental hygiene students - Wahyu Hidayat; Nanan Nur’aeny; Kamilah Winda (DiscoverSys Inc., 2022)
Objective: This study aims to assess the level of HIV/AIDS-related knowledge and stigma among dental hygiene’ students towards people living with HIV/AIDS. Material and Methods: A cross-sectional survey conducted to a senior year dental hygiene student in Politeknik Kesehatan (POLTEKKES) Bandung in November 2019. The sample size determined by a total sampling technique gives rise to 71 participants out of 75 (response rate 94.67%). A self-administered questionnaire was attempted, covered demographic information, participants’ sources of HIV/AIDS knowledge, eleven items concerned to knowledge and five items related to stigma towards PLWHA. Results: The average score for the HIV/AIDS knowledge items and the level of stigma were 8.36 and 3.53. Most of the participants considered as having a high knowledge (71.84%). None of them categorized as a low level of knowledge. Our study also found 66.2% of participants willing to treat PLWHA. Conclusion: The level of HIV/AIDS knowledge considered moderate. However, we still found several mistakes due to the transmission mode of HIV. The stigma’s assessment of PLWHA was low. Nevertheless, unwillingness to live in the same community with PLWHA still indicated.